A robust and efficient method for estimating enzyme complex abundance and metabolic flux from expression data. (December 2015) - Barker, Brandon E.; Sadagopan, Narayanan; Wang, Yiping; Smallbone, Kieran; Myers, Christopher R.; Xi, Hongwei; Locasale, Jason W.; Gu, Zhenglong
Abstract : Highlights: A new algorithm can estimate enzyme abundance using gene–protein-reaction rules. A new algorithm uses enzyme abundance to quickly estimate fluxes. The flux estimates enjoy comparably superior predictivity and good robustness. Software packages with modular implementations are available for the algorithms. Abstract: A major theme in constraint-based modeling is unifying experimental data, such as biochemical information about the reactions that can occur in a system or the composition and localization of enzyme complexes, with high-throughput data including expression data, metabolomics, or DNA sequencing. The desired result is to increase predictive capability and improve our understanding of metabolism. The approach typically employed when only gene (or protein) intensities are available is the creation of tissue-specific models, which reduces the available reactions in an organism model, and does not provide an objective function for the estimation of fluxes. We develop a method, flux assignment with LAD (least absolute deviation) convex objectives and normalization (FALCON), that employs metabolic network reconstructions along with expression data to estimate fluxes. In order to use such a method, accurate measures of enzyme complex abundance are needed, so we first present an algorithm that addresses quantification of complex abundance. Our extensions to prior techniques include the capability to work with large models and significantly improved run-time performance even for smaller models, an improved analysis of enzyme complex formation, the ability to handle large enzyme complex rules that may incorporate multiple isoforms, and either maintained or significantly improved correlation with experimentally measured fluxes. FALCON has been implemented in MATLAB and ATS, and can be downloaded from:https://github.com/bbarker/FALCON . ATS is not required to compile the software, as intermediate C source code is available. FALCON requires use of the COBRA Toolbox, also implemented in MATLAB.